Tribological Properties of Steel/Steel, Steel/DLC and DLC/DLC Contacts in the Presence of Biodegradable Oil - Mannan, Abdul; Sabri, Mohd Faizul Mohd; Kalam, Md. Abul; Masjuki, Haji Hassan (Japan Petroleum Institute, 2019)
Tribological properties of tetrahedral diamond-like carbon (ta-C DLC) coating were investigated to assess the effects of the counter surfaces under the boundary condition in the presence of biodegradable oil. The tribological tests were performed using steel/steel, steel/DLC and DLC/DLC contacts, and found that the coefficient of friction was 0.062, 0.059 and 0.048, and the wear loss was 5.57×10–4, 9.81×10–4 and 6.02×10–4 mm3, respectively. DLC/DLC contacts showed the lowest friction coefficient and steel/steel contacts showed the lowest wear. The high wear of steel/DLC compared to the other two contacts might be due to the high affinity between iron and carbon. The high content of oleic acid may maintain the low friction in self-mated ta-C DLC contacts and tribochemical wear was prevented by nano-scale graphitization. Therefore, material combinations are important for tribological properties and canola oil is an effective lubricant for contacts coated with ta-C DLC films. © 2019 Japan Petroleum Institute. All rights reserved.